MAKNA PRAGMATIK PENGGUNAAN KATA GANTI PERSONA DALAM KELUARGA INTI BANJAR - rissari yayuk rissari yayuk (Balai Bahasa Sumatra Barat, 2018)
AbstractThe problems in this study are (1) How does the form of firs personal pronoun in Banjar nuclear family, (2) how does the form of second personal pronoun in Banjar nuclear family, (3) how does the form of third personal in Banjar Nuclear Family. This study aims to (1) describe the form of firs personal pronoun in Banjar nuclear family, (2) describe the form of second personal in Banjar nuclear family (3) describe the form of third personal pronoun in Banjar nuclear family. This study uses descriotive method and observation technique . The data are taken from Januari 2016 until March 2016 at Bakarung Village, Hulu Sungai Selatan region, South Kalimantan. This study uses pragmatic theory. From the analysis it can be concluded that the form of first personal pronoun is expressed by a wife to her husband, it is “ulun”, “saya”. The form of second personal pronoun, Piyan is “ Anda” expressed by a child to her mom, and the form of third personal pronoun “ Sidin” “beliau” is expressed by an older brother or sister to their father.